Testing the monophyly of Heterosperma (Asteraceae, Coreopsideae) - Lizarazu, Mabel Angela (2018)
The genus Heterosperma (Asteraceae, Coreopsideae) currently comprises ten species distributed from Mexico to South America. Molecular phylogenies of the tribe Coreopsideae (including only two species of Heterosperma) pointed out that the genus would not be monophyletic. A molecular phylogenetic analysis including seven species of Heterosperma and related taxa, using plastid and nuclear sequences, was performed. The results indicated that Heterosperma is monophyletic if Coreopsis cyclocarpa is included. As a result, a new combination, Heterosperma mexicanum, is proposed. Morphological analysis of floral trichomes, pappi and cypselae, is presented. A key to related genera and distribution maps are also provided.